Rasio Keuangan dan Respons Harga Saham: Bukti Empiris dari Sektor Transportasi di Indonesia 2020–2024 - Rizqia Nur Salma; Listri Herlina; Ilham Winar Nugroho (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to empirically examine the influence of the Current Ratio, Debt to Equity Ratio, and Return on Assets both simultaneously and partially on Stock Prices of Transportation and Logistics sector companies listed on the Indonesia Stock Exchange, namely PT Samudera Indonesia Tbk (SMDR), PT TEMAS Tbk (TMAS), and PT AirAsia Indonesia Tbk (CMPP). The sampling technique used is purposive sampling, based on the completeness of quarterly financial reports for the 2020–2024 period and the availability of stock price data. This research employs panel data regression analysis using the Fixed Effect Model (FEM) with EViews 12.0 as an analytical tool. The results indicate that the Current Ratio has a positive but not significant effect on stock prices, with a significance value of 0.1492 > 0.05 and a coefficient of 402.5092. The Debt to Equity Ratio also shows a positive but not significant effect, with a significance value of 0.1492 > 0.05 and a coefficient of 2.795. Return on Assets demonstrates a positive and significant effect, with a significance value of 0.0073 < 0.05 and a coefficient of 27.339. Simultaneously, the three variables are proven to significantly influence stock prices.